1967
DOI: 10.1071/bi9671043
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Sugar-Cane. IX.·Factors Affecting Photosynthesis and Sugar Storage

Abstract: SummaryPhotosynthesis in sugar-cane was linearly related to light intensity up to full sunlight when leaf geometry was similar to that of field-grown plants_ Individual leaves orientated at right angles to the incident radiation were saturated at about two-thirds full sunlight irrespective of whether the leaves developed in low or high light intensities.On a short-term basis, the QlO for photosynthesis was 1·1 over the range 8-34°C. Exposure of intact plants to a 17/10°C day and night temperature regime for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

1968
1968
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
0
17
0
5
Order By: Relevance
“…Waldron et al (1967) showed that photosynthetic efficiency fell at low temperatures (17 • C), and culm growth declined but sucrose content continued to increase. After a period of exposure to low temperature, there was a slow partial recovery in the photosynthetic efficiency (Waldron et al 1967) when the plants were once again exposed to higher temperatures.…”
Section: Temperaturementioning
confidence: 99%
“…Waldron et al (1967) showed that photosynthetic efficiency fell at low temperatures (17 • C), and culm growth declined but sucrose content continued to increase. After a period of exposure to low temperature, there was a slow partial recovery in the photosynthetic efficiency (Waldron et al 1967) when the plants were once again exposed to higher temperatures.…”
Section: Temperaturementioning
confidence: 99%
“…Burr et al (1957) observed a reduction of 84 % in the rate of sugarcane photosynthesis when air temperature was reduced from 23.0 to 13.6 °C. Waldron et al (1967) showed that the photosynthetic effi ciency decreased linearly with a decrease in air temperature in the range from 34 to 5 °C. The effects of air temperature on the photosynthesis rate and on the effi ciency of this process are directly related to crop vegetative development (Alexander, 1973).…”
Section: Air Temperaturementioning
confidence: 99%
“…For the negative degree day accumulation for sugarcane, temperatures between 0 and 7 °C should not be considered because below 7 °C carbon assimilation is negatively affected, as is the stomatal conductance and the photosynthetic rate, which determine the magnitude of the gas exchange of the following day Beauclair, 2004, 2009). As a result of the reduction on carbon assimilation, there is a decrease on the sucrose translocation to stalks (Waldron et al, 1967;Grantz, 1989), and there is an accumulation of sucrose in the leaf cells in an attempt to decrease the matric potential and the freezing temperature of the tissues.…”
Section: Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Temperature effects on photosynthesis appear to be variable. Bierhuizen and Slatyer (1964) showed no significant temperature effect on cotton when temperatures were increased from 30 to 40°C, and Waldron, Glasziou, and Bull (1967) obtained a temperature coefficient of 1 . 1 between 8 and 30°C for sugar-cane.…”
Section: (C) Temperature and Humidity Effects On Photosynthesismentioning
confidence: 99%